Efficiency of Phosphate Concentration Reduction in Laundry Wastewater Using Electrocoagulation Method - Yuniar, Dhara; Sugiharto, Agung (Jurnal Teknika, 2025)
Laundry wastewater contains high levels of phosphates derived from detergent additives, such as sodium tripolyphosphate (STPP), which can trigger eutrophication and degrade water quality if discharged directly into water bodies without treatment. This study aimed to evaluate the efficiency of the electrocoagulation method in reducing phosphate concentrations in laundry wastewater and to assess its potential as a practical and environmentally friendly solution for wastewater management. The electrocoagulation process utilized aluminum electrodes with varying voltages (10, 20, and 30 volts) and contact times (30, 60, and 90 minutes). The results showed that the highest efficiency was achieved at 30 volts and a contact time of 90 minutes, with a phosphate concentration reduction of 96.61%, from 0.277 mg/L to 0.009 mg/L. These findings indicate that increasing voltage and contact time accelerates floc formation and enhances phosphate precipitation efficiency. Thus, electrocoagulation proved to be an efficient and environmentally friendly alternative to conventional coagulation, as it requires no additional chemicals and produces less sludge.